Noel Macainsh replies: - Macainsh, Noel (LiNQ (Literature in North Queensland), 2016)
Dear Judith Wright, Thank you for the honour of your response to the articles in LiNQ (Vol. 6, No. 1, 1978). You touch on matters that are indeed broad and deep, certainly more than could be embraced here. In this regard, I look forward to your address to the teachers of English, to be published in Australian Literary Studies. I am a little unsure when you address me collectively, along with my colleagues, as I imagine that they cherish their individuality just as tenaciously as do the writers; in fact some of them are writers, even virtuoso practitioners of the divided self; though for all I know they may not see themselves as divided. I do not know. I will merely comment for myself.